The quality of learning, teaching and the curriculum - McLean, Monica; Ashwin, Paul (Oxford University Press, 2016)
This Chapter addresses three questions: What is good quality university teaching? How can it be achieved? How can it be assessed? To address these questions we start by making a case for a multi-dimensional, rich conceptualisation of teaching, drawing on a substantial body of higher education research that investigates what supports meaningful learning and on Lee Shulman’s notion of ‘pedagogical content knowledge’ to argue for a principled approach to the design of learning, teaching and the curriculum, which brings groups of students into productive relations with bodies of knowledge. Having established an evidence-based conceptualisation of good quality teaching, we turn to contemporary policy efforts to assess the quality of university undergraduate teaching, arguing that globally the current landscape and languages of higher education are shaped by neoliberal discourses that position learning, teaching and curriculum as a technical-rational matter. In this context, measuring quality by way of ‘metrics’ requires the use of proxies for good teaching, which runs the risk of offering an impoverished definition of the quality of teaching in higher education that also privileges certain social groups. We argue that new languages are needed for the academic community to discuss learning, teaching and the curriculum and that, if we want genuinely to enhance the quality of university education, then metrics must be augmented with peer review, case studies and high quality education and training for teaching. The argument that unfolds is underpinned by the assumption that providing all students, whatever institution they attend, with an equally good university education is essential to social justice.